2015
DOI: 10.13164/re.2015.1025
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Color Image Watermarking Scheme Using Entropy and QR Decomposition

Abstract: Internet has affected our everyday life drastically. Expansive volumes of information are exchanged over the Internet consistently which causes numerous security concerns. Issues like content identification, document and image security, audience measurement, ownership, copyrights and others can be settled by using digital watermarking. In this work, robust and imperceptible nonblind color image watermarking algorithm is proposed, which benefit from the fact that watermark can be hidden in different color chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…These techniques embed the digital watermark in colored image. The obtained results of the developed algorithm showed that is robustness and imperceptiblity against various signal operation attack like compression and histogram equalization [4].…”
Section: Related Workmentioning
confidence: 92%
“…These techniques embed the digital watermark in colored image. The obtained results of the developed algorithm showed that is robustness and imperceptiblity against various signal operation attack like compression and histogram equalization [4].…”
Section: Related Workmentioning
confidence: 92%
“…Similarly, entropy is associated with a combination of unidimensional fuzzy classifiers in order to segment images as shown in paper [79] . An entropy-based watermarking scheme is successfully implemented in article [47] , robust against traditional signal processing attacks. Noisy spectral image fusion is the focus of article [87] , in which the authors apply entropy to minimize the negative effects of noise on the selections of image features.…”
Section: A Review On Entropy and Its Applicationsmentioning
confidence: 99%
“…To protect the copyright of color images, Roy and Pal [14] proposed a hybrid robust watermarking scheme that combines SVD with the redundant discrete wavelet transform (RDWT). In [15], Laur et al proposed a robust color image watermarking based on entropy and QR decomposition. The entropy is used to select the image blocks for watermark embedding.…”
Section: Introductionmentioning
confidence: 99%